2017
DOI: 10.1021/acs.jced.6b00985
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Experimental Liquid–Liquid Equilibrium Data for Ternary Systems Using NRTL and GMDH-Type Neural Network

Abstract: In this work, liquid–liquid equilibrium (LLE) data for the ternary systems (water + propionic acid + solvent) were experimentally obtained at atmospheric pressure and 298.2 K. The ternary systems show type-1 behavior of LLE. Cyclopentane, cyclopentanol, 2-octanone, and dibutyl maleate were chosen as solvent and it has been noted that there are no data in the literature on these ternary systems. The consistency of the experimental tie-line data was checked using the Hand and Othmer-Tobias correlation equations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The equilibrium data of aqueous solution of propionic acid with organic solvents have been correlated using both thermodynamic (NRTL) and mathematical (GMDH-type neural network) models by Özmen and co-workers . In conclusion, more equilibrium data have already been reported by our research team.…”
Section: Introductionmentioning
confidence: 93%
“…The equilibrium data of aqueous solution of propionic acid with organic solvents have been correlated using both thermodynamic (NRTL) and mathematical (GMDH-type neural network) models by Özmen and co-workers . In conclusion, more equilibrium data have already been reported by our research team.…”
Section: Introductionmentioning
confidence: 93%
“…34 During the learning process, GMDH applies different polynomial schemes for linking between the input parameters and the nodes of the intermediate layers. 35,36 The hybrid form is considered the most reliable version of GMDH as it brings many advantages in the learning process. 34,37 Application of higher-order polynomials and the interaction between the different nodes regardless of their positions are among the specificities ensuring the flexibility and the accuracy of the hybrid version of GMDH.…”
Section: Group Methods Of Data Handlingmentioning
confidence: 99%
“…11−14 Mainly, hydrocarbons and halogenated hydrocarbon, 15−17 ketones, 18−22 heavy alcohols, 23−28 esters and dibasic esters, 29−32 nitriles, 33,34 and ethers 35 have been examined for the LLE measurements. In the latest investigations, O ̈zmen and co-worker 36 have reported further equilibrium data for the related PA containing systems.…”
Section: ■ Introductionmentioning
confidence: 93%
“…In the earliest investigations, several authors have reported many LLE data on systems containing water, PA, and organic solvents from different chemical categories. Subsequently, important studies have been carried out on the acid extraction from water and LLE measurements by several researchers. Mainly, hydrocarbons and halogenated hydrocarbon, ketones, heavy alcohols, esters and dibasic esters, nitriles, , and ethers have been examined for the LLE measurements. In the latest investigations, Özmen and co-worker have reported further equilibrium data for the related PA containing systems.…”
Section: Introductionmentioning
confidence: 94%